Effect of Heating Methods on Quality Attributes of Culled Saanen Crossbred Goat Meat - PUTRA, Aronal Arief; WATTANACHANT, Saowakon; WATTANACHANT, Chaiyawan (Walailak Journal of Science and Technology (WJST), 2017)
The effect of boiling, grilling, and microwaving until reaching temperature of 85 °C on culled Saanen goat meat was evaluated and compared to raw samples. Biceps femoris muscle was used to evaluate the effect of these heating methods on proximate composition, collagen, cook loss, color, and texture profile analysis. Supraspinatus muscle was used to determine the effect of these heating methods on changes in peroxide value (PV) and thiobarbituric acid reactive substances (TBARS) of meat during 5 days of chilled storage. Boiled and grilled samples showed lower moisture (63.04 and 63.89 %, respectively) and higher protein (29.20 and 29.59 %, respectively) and fat (5.98 and 4.01 %, respectively) than those of the microwaved sample (68.03 % moisture, 26.72 % protein, and 2.95 % fat) (P < 0.05). Higher total collagen in the grilled sample (14.35 mg/g) and higher soluble collagen percentage (6.57 %) in the microwaved sample were obtained (P < 0.05). Boiled and grilled samples revealed higher cook loss (39.70 and 41.28 %, respectively) compared to microwaved samples (28.82 %) (P < 0.05). Grilled samples exhibited higher hardness (3,730.21 g), gumminess (2,397.76), and chewiness (1,774.71) than those of other heated samples (P < 0.05). Higher lightness (L* = 54.90), lower redness (a* = 4.11) and yellowness (b* = 13.96) in boiled sample were found (P < 0.05). Grilled samples exhibited sharper PV formation while boiled samples revealed sharper TBARS formation during storage (P < 0.05). In summary, variation in remaining moisture, soluble collagen, parallel with types of heating medium led to complexity in the results obtained in total solid, cook loss, color, and texture profile analysis (TPA). Boiled samples were prone to yield higher TBARS formation.